2023
DOI: 10.1021/acsami.3c01742
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochromic Regulation for Near-Infrared and Visible Light via Porous Tungsten Oxide Films with Core/Shell Architecture

Abstract: Dual-band electrochromic smart windows have become a research hotspot owing to their unique ability to selectively control near-infrared (NIR) and visible (VIS) light. However, the design and exploitation of dual-band electrochromic films are still an extreme challenge due to the scarcity of relevant high-performance materials. To solve this issue, we here proposed a type of porous WO 3 film with nanowires/nanoparticles core/ shell architecture as a promising candidate, endowing smart windows with a dual-band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 54 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…With the increase of the applied voltage, the Li ions are apt to be diffused in the lattice, resulting in new absorption transitions in the VIS light. 23,24 At −0.5 V, the transmittance is only 2.6% at 633 nm and 0.05% at 1050 nm, respectively. In the dark mode, neither VIS nor NIR light can pass through the film, keeping the room dark and cool.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…With the increase of the applied voltage, the Li ions are apt to be diffused in the lattice, resulting in new absorption transitions in the VIS light. 23,24 At −0.5 V, the transmittance is only 2.6% at 633 nm and 0.05% at 1050 nm, respectively. In the dark mode, neither VIS nor NIR light can pass through the film, keeping the room dark and cool.…”
Section: Resultsmentioning
confidence: 98%
“…At −0.01 V, Li ions are mainly adsorbed on the nanosheet surface to form LSPR, which is difficult to insert into the lattice. , In the cool mode, the transmittance of 3% TiWH45 is 2.6% at 1050 nm and 49.7% at 633 nm, the NIR region was shielded by the 3% TiWH45 film, while VIS light can pass through the film, maintaining a bright and cool indoor environment. With the increase of the applied voltage, the Li ions are apt to be diffused in the lattice, resulting in new absorption transitions in the VIS light. , At −0.5 V, the transmittance is only 2.6% at 633 nm and 0.05% at 1050 nm, respectively. In the dark mode, neither VIS nor NIR light can pass through the film, keeping the room dark and cool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 8a–e, Cai et al 70 recently prepared a type of porous WO 3 film with nanowires/nanoparticles core/shell architecture as a promising candidate for smart windows with a dual-band electrochromic feature. The results indicated that the dual-band electrochromic performance was credited to the progressive electrochemical reduction procedure, in which the capacitive charging process gave rise to NIR regulation and the following ion intercalation contributed to VIS light modulation.…”
Section: Inorganic Nanomaterials For Ec Devicesmentioning
confidence: 99%
“…To date, a range of wet methods has been used for the attempted fabrication of WO 3 films, including chemical bath deposition, 25 electrodeposition, 26 hydrothermal, 27 solvothermal and sol-gel methods. 28,29 Among them, the hydrothermal technique offers attractive opportunities for fabricating WO 3 films with various crystal structures and morphologies.…”
Section: Introductionmentioning
confidence: 99%